2014
DOI: 10.1016/j.ajpath.2013.12.023
|View full text |Cite|
|
Sign up to set email alerts
|

VEGFA Activates Erythropoietin Receptor and Enhances VEGFR2-Mediated Pathological Angiogenesis

Abstract: Clinical and animal studies implicate erythropoietin (EPO) and EPO receptor (EPOR) signaling in angiogenesis. In the eye, EPO is involved in both physiological and pathological angiogenesis in the retina. We hypothesized that EPOR signaling is important in pathological angiogenesis and tested this hypothesis using a rat model of oxygen-induced retinopathy that is representative of human retinopathy of prematurity. We first determined that EPOR expression and activation were increased and that activated EPOR wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 49 publications
3
40
1
Order By: Relevance
“…In this regard, EpoR is known to establish physical interactions with other cytokine receptors, in particular, with members of the Receptor Tyrosine Kinase (RTK) family, such as c-Kit [40] and VEGFR [41]. It has been reported that activation of these RTKs by their cognate ligands, stem cell factor and VEGF, respectively, brings EpoR in physical proximity, thereby inducing its transphosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, EpoR is known to establish physical interactions with other cytokine receptors, in particular, with members of the Receptor Tyrosine Kinase (RTK) family, such as c-Kit [40] and VEGFR [41]. It has been reported that activation of these RTKs by their cognate ligands, stem cell factor and VEGF, respectively, brings EpoR in physical proximity, thereby inducing its transphosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from the study hypothesized that increase in the expression and activation of EPOR can be triggered by VEGF-A, present in the vascular endothelium, upon binding to VEGF receptor-2 (VEGFR-2). 34,36,51 Phosphorylated VEGFR-2 then interacts with phosphorylated EPOR to enhance angiogenesis via a STAT3 signaling pathway 51 and this was equally reported by Nakano et al, 52 Sautina et al, 53 and Yang et al 54 In conclusion, the EPO also modulates angiogenesis by inducing the secretion of VEGF, which then binds and activates VEGFR-2. [51][52][53][54] Apart from VEGFR-2, Sautina et al 53 also demonstrated that the stimulation of EPO is dependent on the βcR.…”
Section: The Role Of Epo In the Eyementioning
confidence: 88%
“…39,53 This study proposed that NO stimulation was regulated by the heterotrimeric interaction between EPOR/βcR/VEGF-R2 upon binding of EPO to EPOR/βcR. 39,[51][52][53][54][55] Meanwhile, studies have reported that genetic polymorphism in the EPO gene may be a pathogenic factor for acquiring risk of proliferative DR. 56 Katsura et al 55 showed that vitreous EPO was present in significantly higher amount in proliferative DR patients than in macular hole patients who had no retinopathy. The authors further showed the high EPO concentration was not induced by systemic anemia.…”
Section: The Role Of Epo In the Eyementioning
confidence: 99%
“…35 Repeated fluctuations in oxygen delivery in animal models leads to increased oxidative compounds, 36 over-expression of VEGF and VEGF receptor 2 and also over-activation of signaling cascades involving VEGFR2. 3,37 Besides fluctuations in oxygenation, risks for human ROP have included associations with poor infant growth 38 and increased oxidative stress. 3941 …”
Section: Current Treatment For Rop and Reasons For Better Therapiesmentioning
confidence: 99%
“…Over the past several decades, vascular endothelial growth factor (VEGF) has become recognized as an important pathologic angiogenic factor in a number of eye diseases, including age-related macular degeneration (AMD), 13 diabetic retinopathy, 4,5 retinal vein occlusion, 4 and retinopathy of prematurity (ROP). Prior to FDA approval of anti-VEGF agents for AMD, a disease affecting elderly adults, preclinical studies tested VEGF inhibitors in animal models of angiogenesis, including models of oxygen-induced retinopathy (OIR) in which blood vessels grow into the vitreous cavity similar to what occurs in diabetic retinopathy and ROP.…”
Section: Introductionmentioning
confidence: 99%